African Financial Development Dynamics: Big Time Convergence - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2012)
Purpose - Assessment of African financial development dynamic convergences in money, credit, efficiency and size. Design/Methodology - The empirical evidence is premised on 11 homogenous panels based on regions (Sub-Saharan and North Africa), income-levels (low, middle, lower-middle and upper-middle), legal-origins (English common-law and French civil-law) and religious dominations (Christianity and Islam). We examine convergence in financial intermediary dynamics of depth, efficiency, activity and size. Findings - Findings suggest that countries with small-sized financial intermediary depth, efficiency, activity and size are catching-up countries with large-sized financial intermediary depth, efficiency, activity and size respectively. We also provide the speeds of convergence and time necessary to achieve a full (100%) convergence. Practical implications - The presence of strong links among African banking sectors may present little opportunity for portfolio diversification. The convergence patterns show positive steps towards regional integration. As a policy implication, African governments should not relent in structural and institutional reforms. Originality/value - It is the first critical assessment of convergence in financial intermediary development dynamics in the African continent.
Keywords: F15; F36; F42; O55; P52; 330; Convergence; Policy Coordination; Banking; Africa